2021
DOI: 10.2147/dmso.s308390
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Relationship Between Serum 25-Hydroxyvitamin D and Urine Albumin to Creatinine Ratio in Type 2 Diabetes: A Cross-Sectional Study in China

Abstract: Background: Diabetic kidney disease often presents as increased urine albumin to creatinine ratio (UACR). 25-hydroxyvitamin D (25(OH)D) is considered as the best indicator of vitamin D status. Previous studies have shown that 25(OH)D is related to the UACR. However, evidence concerning the connection between 25(OH)D and UACR is still limited in the Chinese population. Materials and Methods: A total of 549 participants with type 2 diabetes were enrolled in the study from Shenzhen People's Hospital, China. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In agreement with our results, Alatawi et al (19) elucidated that diabetic rats showed a significant decrease in SOD and GPx but a significant elevation in MDA, the situation was reversed after treatment of diabetic rats with vitamin D supplementation indicating that vitamin D played a crucial role in the protection of tissues from damage by free radicals. Furthermore, we noticed inverse relationship between vitamin D and UACR, a finding supported by Liang et al (20) .…”
Section: Discussionsupporting
confidence: 88%
“…In agreement with our results, Alatawi et al (19) elucidated that diabetic rats showed a significant decrease in SOD and GPx but a significant elevation in MDA, the situation was reversed after treatment of diabetic rats with vitamin D supplementation indicating that vitamin D played a crucial role in the protection of tissues from damage by free radicals. Furthermore, we noticed inverse relationship between vitamin D and UACR, a finding supported by Liang et al (20) .…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies were mainly focused on T2DM population to explore the relationship of VD levels and the presence of DKD ( 12 , 13 , 28 ). Recent studies have indicated that hypovitaminosis D was associated with a higher risk of developing DKD in T2DM ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it plays a vital role in modulating cell proliferation, apoptosis, differentiation, inflammation response, immune function, and vascular and metabolic properties such as insulin secretion and insulin sensitivity (8)(9)(10). 25hydroxyvitamin D [25(OH)D] is synthesized by 25-hydroxylase catalyzing VD, which is considered as the best indicator of VD status (11,12). In recent years, lower serum 25(OH)D level has been implicated in the incidence of T2DM, which may rely on its association with impaired glucose and insulin metabolism (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with DKD are more likely to be vitamin D deficient than those without DKD [ 6 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. A cross-sectional study involving 300 patients with diabetes found that CKD was significantly associated with vitamin D deficiency ( p = 0.043).…”
Section: Role Of Vitamin D In Management Of Diabetic Kidney Diseasementioning
confidence: 99%